2015
DOI: 10.1109/tie.2014.2354597
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis Losses in Sintered NdFeB Permanent Magnets in Rotating Electrical Machines

Abstract: Permanent magnet materials are nowadays widely used in the electrical machine manufacturing industry. Eddy current loss models of permanent magnets used in electrical machines are frequently discussed in research papers. In magnetic steel materials we have, in addition to eddy current losses, hysteresis losses when AC or a rotating flux travels through the material.Should a similar phenomenon also be taken into account in calculating the losses of permanent magnets? Actually, every now and then authors seem to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…There is a wide variety of analytical and numerical techniques for PM loss prediction [58]- [89]. The analytical techniques are based on simplified assumptions regarding the magnetic field distribution within the machine assembly, and their use is usually limited to the selected machine topologies and operating regimes.…”
Section: ) Permanent Magnet Power Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a wide variety of analytical and numerical techniques for PM loss prediction [58]- [89]. The analytical techniques are based on simplified assumptions regarding the magnetic field distribution within the machine assembly, and their use is usually limited to the selected machine topologies and operating regimes.…”
Section: ) Permanent Magnet Power Lossmentioning
confidence: 99%
“…These PM loss components are attributed mainly to the eddy-currents effects (Joule losses). The hysteresis loss effects in the PM material have been found to be negligible [89].…”
Section: ) Permanent Magnet Power Lossmentioning
confidence: 99%
“…For some applications, especially in high-speed machines, they could become a problem [16]. In [17], it is concluded that hysteresis loss in permanent magnets do not play any significant role in electrical machines.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are both eddy-current loss component and hysteresis loss component occur in PMs [15], researchers always focus on eddy-current loss, with hysteresis ignored. When reviewing the existing techniques of predicting magnet loss in the rotors of PM machines, two main methods have emerged: numerical and analytical [10], [16]- [36].…”
Section: Introductionmentioning
confidence: 99%
“…This is exacerbated by difficulty of predicting rotor temperature; the rotary rotor assembly does not allow for a simple and reliable temperature monitoring and protection. Furthermore, the continuous drive towards high power-density and compact PM machine solutions imposes the requirement of elevated temperature operation to fully utilise physical properties of the active materials used.Although there are both eddy-current loss component and hysteresis loss component occur in PMs [15], researchers always focus on eddy-current loss, with hysteresis ignored. When reviewing the existing techniques of predicting magnet loss in the rotors of PM machines, two main methods have emerged: numerical and analytical [10], [16]-[36].…”
mentioning
confidence: 99%